Effect of 60∘ dislocation on transformation stresses, nucleation, and growth for phase transformations between silicon I and silicon II under triaxial loading: Phase-field study. (15th September 2019) - Babaei, Hamed; Levitas, Valery I.
Abstract: Stress-induced martensitic phase transformations (PTs) at a stationary 60 ∘ dislocation in single-crystalline Si are modeled by an advanced phase-field approach (PFA), which takes into account the lattice instability conditions obtained by atomistic simulations for the general stress tensor. Finite elastic, transformation, and plastic strains are considered. Finite element method (FEM) simulations elucidate two different mechanisms of nucleation and nanostructure evolution for two different stress-hysteresis cases. For a traditional finite-stress-hysteresis region, the PT starts with the barrierless nucleation of a thermodynamically-equilibrium-incomplete embryo, which loses its stability and grows forming a propagating martensitic band with distinct interfaces. However, in the unique zero-stress-hysteresis region, where PT for defect-free crystal occurs homogeneously through intermediate phases without nucleation, interfaces, and growth, the PT starts at a dislocation but spreads quasi-homogeneously, without interfaces, similar to the defect-free case; the macroscopic stress-strain curve is horizontal and without hysteresis during direct-reverse PTs. Despite large normal stresses produced by dislocation in the range of ± ( 6 − 12 ) GPa, a relatively small reduction in macroscopic PT stress by 1.6 GPa is quantitatively explained by mutually compensating contributions of stresses into lattice instability criterion. Graphical abstract: Image 1